The performance of nurses: practices, potential and weaknesses in high-risk prenatal care - Ribeiro, Ellen Eduarda Santos; Pereira, Lívia Carvalho; Rocha, Girzia Sammya Tajra; Ferreira Júnior, Antonio Rodrigues; Magalhães, Rosilane de Lima Brito; Jorge, Herla Maria Furtado (Revista de Enfermagem da UFPI, 2024)
Objective: To analyze the potential and weaknesses of nurses in the provision of high-risk prenatal care. Methods: Qualitative research, carried out with six nurses from the high-risk outpatient clinic of a reference maternity hospital in the municipality of Teresina, Piauí. Data were collected from February to March 2020 through semi-structured interviews and examined according to content analysis. Results: Nurses can provide high-risk prenatal care with emotional support, embracement and educational practices that directly impact maternal morbidity and mortality. The potentialities were the adequate physical space and the length of service in the institution and the fragility was the lack of nursing consultation. Conclusion: It was evidenced that nurses do not fully develop all the practices recommended by the Ministry of Health. Despite this, there is potential in the performance, namely, their acquired knowledge, and physical space, and the materials. These aspects facilitate the development of care practices that can promote a healthy birth and reduce maternal mortality. In addition, nurses aim for recognition and greater protagonism in specialized prenatal care.